PENGARUH MANAJEMEN STRATEJIK SUMBER DAYA MANUSIA TERHADAP INOVASI DENGAN MANAJEMEN PENGETAHUAN SEBAGAI VARIABEL MEDIASI - Muhammad Harri (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2021)
The purpose of this research is to analyze the relationship of human resource strategic management and innovation, human resource strategic management and knowledge management, knowledge management and innovation, in addition to analyzing whether knowledge management can mediate the relationship of human resource strategic management with innovation Research data to be used is data of creative industry companies in Indonesia with primary data through questionnaires and secondary data published by the Government of Indonesia. The research sample is a creative industry company in Indonesia. The methods used are correlation analysis and regression to find out the relationship between variables and the analysis of pathways to find out the direct effects and indirect effects of human resource strategic management on innovation. The hypothesis of this research is (1) there is a positive relationship of human resource strategic management with innovation, (2) there is a positive relationship between the strategic management of human resources and knowledge management (3) there is a relationship between knowledge management and innovation (4) there is a positive relationship of human resource strategic management to innovation through knowledge management as a mediation variable. The findings provide evidence that knowledge management plays a mediating role between strategic human resource management and innovation.